2021
DOI: 10.1007/s00405-021-06839-w
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported smell and taste recovery in coronavirus disease 2019 patients: a one-year prospective study

Abstract: Purpose The aim of the present study was to estimate the 1 year prevalence and recovery rate of self-reported chemosensory dysfunction in a series of subjects with previous mild-to-moderate symptomatic COVID-19. Methods Prospective study based on the SNOT-22, item “sense of smell or taste” and additional outcomes. Results 268/315 patients (85.1%) completing the survey at baseline also completed the follow-up interview. The 12 months prevalenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 22 publications
10
92
4
Order By: Relevance
“…Consistent with several other studies, our study corroborates that dysfunctions of taste and smell are early onset symptoms of COVID-19 [22][23][24][25] and persist in many cases for several months [13,[26][27][28]. It was evident that qualitative changes (parosmia, phantosmia and dysgeusia) can occur as late-onset symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with several other studies, our study corroborates that dysfunctions of taste and smell are early onset symptoms of COVID-19 [22][23][24][25] and persist in many cases for several months [13,[26][27][28]. It was evident that qualitative changes (parosmia, phantosmia and dysgeusia) can occur as late-onset symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…However, many geographic differences have been reported and the overall prevalence worldwide is around 46% [8]. The first studies with 6-month follow-up reported that 5% to 11.7% of patients presented severe long-term OD and GD, meaning that we can expect have a high number of patients with disabling disorders in the next few years [9][10][11][12][13]. However, this data must be interpreted with caution as there are significant differences based on the assessment methodology [14] (e.g., objective versus subjective tests) and in no study it is possible to exclude that patients unknowingly presented an OD before COVID-19 [15].…”
Section: Introductionmentioning
confidence: 99%
“…In defiance of this well-known healing capability of the OE, however, a significant number of COVID-19 convalescents experience persistent ODs lasting for 12 months or longer [22][23][24][25]. The absent or exceptionally retarded recovery from COVID-19 ODs in those individuals implies a more severe or lasting damage to the OE by SARS-CoV-2.…”
Section: Persistent Anosmia Hyposmia or Parosmiamentioning
confidence: 99%
“…The incidence of smell and/or taste impairment in COVID-19 patients varied from as low as 5% to as high as 98% in the literature, depending on areas, populations, SARS-CoV-2 variants, and methods of diagnosis, but most analyses have reported an OD rate of 20-80% [11][12][13][14][15][16][17][18][19][20][21]. Although a Viruses 2021, 13, 2225 2 of 15 majority of COVID-19-related ODs disappear in a few weeks, the deficits in some patients could persist long after resolution of other COVID-19 abnormalities [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%